EVI/WLS function is regulated by ubiquitylation and is linked to ER-associated degradation by ERLIN2 - Wolf, Lucie; Lambert, Annika M.; Haenlin, Julie; Boutros, Michael (Journal of cell science, 2021)
WNT signalling is important for development in all metazoans and is associated with various human diseases. The ubiquitin-proteasome system (UPS) and regulatory endoplasmic reticulum-associated degradation (ERAD) have been implicated in the production of WNT proteins. Here, we investigated how the WNT secretory factor EVI (also known as WLS) is ubiquitylated, recognised by ERAD components and subsequently removed from the secretory pathway. We performed a focused immunoblot-based RNAi screen for factors that influence EVI/WLS protein stability. We identified the VCP-binding proteins FAF2 and UBXN4 as novel interaction partners of EVI/WLS and showed that ERLIN2 links EVI/WLS to the ubiquitylation machinery. Interestingly, we also found that EVI/WLS is ubiquitylated and degraded in cells irrespective of their level of WNT production. This K11, K48 and K63-linked ubiquitylation is mediated by the E2 ubiquitin-conjugating enzymes UBE2J2, UBE2K and UBE2N, but is independent of the E3 ubiquitin ligases HRD1 (also known as SYVN1) and GP78 (also known as AMFR). Taken together, our study identifies factors that link the UPS to the WNT secretory pathway and provides mechanistic details of the fate of an endogenous substrate of regulatory ERAD in mammalian cells.This article has an associated First Person interview with the first author of the paper.
Gesehen am 02.11.2021